1992
DOI: 10.1093/jnci/84.24.1875
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Angiogenesis: A New Significant and Independent Prognostic Indicator in Early-Stage Breast Carcinoma

Abstract: Such an indicator would be useful in selection of those node-negative patients with breast carcinoma who are at high risk for having occult metastasis at presentation. These patients could then be given systemic adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

38
902
9
28

Year Published

1994
1994
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,655 publications
(977 citation statements)
references
References 0 publications
38
902
9
28
Order By: Relevance
“…It is also thought that the degree of tumour angiogenesis is related to clinical outcome, suggesting that angiogenic properties are correlated with tumour aggressiveness (Bosari et al, 1992;Weidner et al, 1992;Gasparini et al, 1994). In a previous study (Maeda et al, 1995) we also demonstrated that the microvessel count is an independent prognostic indicator in patients with gastric carcinoma.…”
supporting
confidence: 53%
“…It is also thought that the degree of tumour angiogenesis is related to clinical outcome, suggesting that angiogenic properties are correlated with tumour aggressiveness (Bosari et al, 1992;Weidner et al, 1992;Gasparini et al, 1994). In a previous study (Maeda et al, 1995) we also demonstrated that the microvessel count is an independent prognostic indicator in patients with gastric carcinoma.…”
supporting
confidence: 53%
“…The slides were treated as above for the final steps of immunohistochemistry. Vessel counts on histological slides were performed according to a method described by Weidner et al 47 for tumors. Since these tissues are usually associated with a high vessel count, we have adapted this method.…”
Section: Elisa Quantification Of Bfgf In Vivomentioning
confidence: 99%
“…8,10,12 HIF-1 expression may have prognostic and therapeutic consequences because angiogenesis is a prognostic indicator. 13,14 Although the precise mechanism, and especially the initiation, of tumor angiogenesis is not understood fully, antiangiogenic therapies are under rapid development and clinical evaluation. 15 Along with intratumoral microvessel density, increased VEGF expression is associated with a poor prognosis; therefore.…”
mentioning
confidence: 99%